J.P. AMALRIC, B. BENNASSAR, A. BRODER, G.CHASTAGNARET, J.P. DEDIEU, L. DOMERGUE, J. PÉREZ, E. TEMINE: Aux origines du retard économique de L'Espagne XVI - XIX siécles. - Diego García, Emilio de (Cuadernos de Historia Moderna y Contemporánea, 1984)
Sin resumen